Recombinational basis of serovar diversity in Salmonella enterica. - Li, J (1994)
The fliC gene, which encodes phase 1 flagellin, was sequenced in strains of 15 Salmonella enterica serovars expressing flagellar antigenic factors of the g series. The occurrence of each of the flagellin serotypes g,m, m,t, and g,z51 in distantly related strains is the result of horizontal exchange of DNA, as indicated by identity or close similarity in nucleotide sequence of all or parts of the antigenic factor-determining central region of fliC. The flagellin genes of some serovars are complex mosaic structures composed of diverse segments derived through multiple recombination events. Thus, recombination of horizontally transferred segments (intragenic) or entire genes (assortative) within and among subspecies is identified as a major evolutionary mechanism generating both allelic variation at the fliC locus and serovar diversity in natural populations. Evidence that flagellar serological diversity is promoted by diversifying selection in adaptation to host immune defense system or flagellotropic phage is discussed.